Effects of probiotic supplementation on broiler performance - A. H., Ramlah; C. K., Tan (Universiti Putra Malaysia Press, 1995)
A study on the effect of probiotic supplementation on broiler performance was carried out with 600 one day-old Avian broiler chicks. The duration of study was 35 days and a commercially prepared lactobacillus culture was given to the treated birds via drinking water throughout the 35 days. The results showed that the live weight of the treated bird was significantly (P<0.05) improved at 21, 28 and 35 days of age. Feed conversion ratio of the treated bird was significantly (P<O. 05) improved after the first week. The treated bird had a better, but not significantly different, daily live weight gain and total feed intake than the control bird. Probiotic supplementation via drinking water increases the income of the broiler farmer by as much as 11.76 cents/bird.